Noise assessment at construction site which uses IBS formwork system - Abas, Nor Haslinda; Mohd Ta’at, Nurul Hasanah; Hasmori, Muhammad Fikri; Abdullah, Abd.Halid; Nagapan, Sasitharan; Deraman, Rafikullah; Yean, Ghing Tong; Hardono, Setiawan (Politeknik Malaysia, 2018)
This study measures the noise level that construction workers are exposed to at construction site while performing the activities in the construction of building envelop at Putrajaya, which uses IBS formwork system as a construction method. This study involved three phases, in-line with the research objective. The first phase involved identifying the process involved in the construction of building envelop together with the potential associated noise hazards. This was done through field and interview with the project personnel. The second phase involved assessing the noise exposure for affected activities using Sound Level Meter (SLM). Next, the noise profile is plotted throughout the construction stage (Phase III). Informal interview was also conducted with the workers who exposed to the high noise to know whether the noise exposure while doing works affect their health. The analysis showed that, even though the average highest level of noise recorded was 103.8dB (at 1m distance), the workers were not exposed to the level of noise of more than 115dB at the selected construction site. This means that, for this particular construction site, the level of noise that the workers are exposed to while working will not endanger them in a short period of time.